Craniosynostosis‐microphthalmia syndrome belongs to the spectrum of BCOR‐related disorders. Issue 4 (3rd August 2020) - Cinnirella, Giacomo; Taylor, Rachel L.; Coco, Claudio; Piludu, Francesca; Vidiri, Antonello; Sinibaldi, Lorenzo; Kornak, Uwe; Black, Graeme; Brancati, Francesco
Abstract : Craniosynostosis‐microphthalmia linked to BCOR haploinsufficiency.